Nota sobre a extração de óleo de abacates pelo processo a quente e úmido - Ferreira , Elmo (Revista Ceres, 2025)
A new method of extracting avocado oil using heat and additional water was studied. The purpose of this study was to test the feasibility of a new industrial processing technique of avocado oil extraction which consisted of pulping, initial heating, addition of water, second heating, and finally centrifugation of the "avocado milk".